Shaft Fractures of the Metacarpus and Metatarsus in Cattle - Steiner, A.; Iselin, U.; Auer, J. A.; Lischer, C. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
This study describes the history, signalment, fracture configuration, methods of treatment and outcome of 58 cattle suffering from a shaft fracture of the metacarpus or metatarsus. For the purpose of describing the accuracy of fracture reduction and progress of healing, as defined by radiographs, a grading system was developed and is described.Of the 58 animals, 17 (29.3%) were treated by means of a full-limb cast, seven (12.1%) by a walking-cast, 13 (22.4%) by a modified walking-cast, and 11 (19.0%) by open reduction and internal fixation (ORIF). Ten animals (17.2%) were slaughtered, because of economic reasons, immediately after the diagnosis had been confirmed. The (modified) walking-cast techniques were more frequently used for treatment of complex fractures; full-limb cast and ORIF were more frequently used for the other fracture types. Radiographic long-term followup data revealed that ORIF provided significantly better long-term results than external coaptation. An angular limb deformity in the saggital plane (plantar bowing) occurred in three of four metatarsal, but not in metacarpal fractures treated by external coaptation. A significant correlation existed between the quality of fracture reduction and the long-term result. However, a correlation was not found between the age and body weight of the animals and the outcome, and between the time from trauma to treatment and the outcome.Fifty-eight shaft fractures of the metacarpus and metatarsus in cattle were evaluated retrospectively using a new radiographic scoring system. Open reduction and internal fixation provided significantly better long-term results than external coaptation. A significant correlation was found between the quality of the fracture reduction and the long-term result; a correlation was not found between age and body weight of the animal and the outcome, nor between the time that elapsed from trauma to treatment and the outcome.
Keywords: Cattle; metacarpus; metatarsus; shaft fracture; radiographic scoring system